Consumer perception about edible insects’ relation with environment and sustainability - Guiné, Raquel P. F. (2024)
Edible insects have been suggested as a potential environmental and economic solution to replace less sustainable conventional protein sources for human nutrition. Hence, this work investigated the perceptions and knowledge of consumers in fourteen different countries towards edible insects and their relation with environment and sustainability. For that, data were collected through a questionnaire survey in the ambit of the EISuFood Project, and 7221 responses were obtained. The results showed that although participants had some difficulty in identifying wrong statements, a majority were able to express disagreement towards them (ex. comparison between poultry and insect productions for water requirements, comparison between pork and insect productions for area requirements). A great majority of respondents showed agreement with true statements, like insect production emits fewer greenhouse gases than beef production. Higher percentages of respondents that did not manifest a decisive opinion were found for insects being able to efficiently convert organic matter into protein, or for loss of biodiversity being lower for insect compared to other animal productions. Sociodemographic variables sex and education were significantly influenced knowledge on most of the questions, while age was not found so influential. Regarding the geographic variable living environment, it significantly influenced the knowledge on practically all items, and country significantly influenced knowledge in all of the questions, being the most influential of all variables studied. As a conclusion, it was fund that perception about edible insects and sustainability are influenced by sociodemographic characteristics of the participants and greatly variable according to geographical factors.